Climate change commitments and agriculture sectoral strategies in Cameroon: Interplay and perspectives - Chia, E.L.; Sufo-Kankeu, R.; Hubert, D. (Informa UK Limited, 2019)
Cameroon like other developing countries is developing approaches to respond to national and global climate change adaptation and mitigation commitments. Sufficient information on the interplay between sector policies and the causes, impacts and response to climate change is relevant for developing sustainable climate change response plans. Using the agriculture sector as a case, this paper examines this interplay in the context of the humid forest zone (HFZ) of Cameroon. Drawing on secondary information from agriculture sector strategies, forest cover change, climate vulnerability and agriculture systems in the HFZ, we found that: (i) the objectives of agriculture expansion and avoided deforestation and forest degradation are at cross-roads; (ii) agriculture as a livelihood strategy is vulnerable to climate variability and change; (iii) strengthening agriculture production systems technically, materially and financially are main suggestions for climate resilient and low carbon emission agriculture practices. We highlight barriers that need to be addressed for the agriculture intensification mechanism, i.e. the agriculture research and extension services in Cameroon to respond to the needs of adaptation and carbon emission reductions from avoided deforestation. These barriers and others would be addressed if their financial, technology and capacity building needs are carefully evaluated as Cameroon mobilizes resources for the implementation of its National Determined Contributions.